INDIA- LOCATION - mahak (Innovative Research Thoughts, 2017)
India, also known as Bharat or Hindustan, is one of the world's most culturally and geographically diverse regions. India is home to over 17.5% of the world's population, making it the second most populated nation. However, the nation only makes up 2.42 percent of the global landmass.